Emphasizing Food Expenditure as a Food Waste Mitigation Initiative at Restaurants in Banyumas, Indonesia - Ibtiyah, Anggita Khoerutul; Romadlon, Fauzan; Nurisusilawati, Isnaini (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2023)
Food waste can be defined as waste at the final stage of the food supply chain related to retailers and consumer behavior (distribution and market, consumption). The population expected to increase over the years, will also affect food availability and consumption. The problem can be solved by increasing food production, but it does not help much if the quantity of loss and waste is not minimized. In Indonesia, consumption activities are not only to fulfill hunger but also become a lifestyle such as visiting restaurants. Restaurants have a high potential to create food waste and in Banyumas the restaurant contribute more waste after households. the study aims to find the role of food expenditure at restaurant to reach food waste management initiatives. It relates to how restaurants see food expenditures as a strategy to procure and sell the menu based on portion adjustment. The method used was quantitative and obtained data by distributing questionnaires to 103 restaurants in Banyumas using ANOVA. The result showed the demographics affect food expenditure at restaurants in Banyumas. The restaurants can conduct food waste mitigation initiatives by enhancing restaurant services, adjusting the meal menu with consumers, forecasting procurement quantity, considering storage for raw material, and focusing on food consumption. Furthermore, the restaurant shall consider to manage menu to avoid food waste by adding more refrigerator or utilizing the waste.